2022
DOI: 10.1057/s41599-022-01287-1
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to climate change risk: classification of and transitions in the UK population between 2012 and 2020

Abstract: Strategies for achieving carbon emissions goals presuppose changes in individual behaviour, which can be indirectly nudged by interventions or tailored information but ultimately depend upon individual attitudes. Specifically, the perception that climate change is low risk has been identified as a barrier to participation in climate change adaptation and mitigation efforts. Therefore, understanding public attitudes towards climate change risk is an important element of reducing emissions. We applied k-means cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 98 publications
(128 reference statements)
2
5
0
Order By: Relevance
“…For example, Rhead et al [10], using the UK Survey of Public Attitudes and Behaviour towards the Environment, found evidence that greater environmental concern led to the higher probability of being engaged in pro-environmental behaviour. This finding was supported by Liu et al [11], who explored attitudes to climate change risk using the UK Household longitudinal study for 2012 and 2020. Liu et al [11] identified the temporal stability of cluster structure between two surveys in 2012 and 2020 in the UK, noting the shift towards the Concerned cluster.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…For example, Rhead et al [10], using the UK Survey of Public Attitudes and Behaviour towards the Environment, found evidence that greater environmental concern led to the higher probability of being engaged in pro-environmental behaviour. This finding was supported by Liu et al [11], who explored attitudes to climate change risk using the UK Household longitudinal study for 2012 and 2020. Liu et al [11] identified the temporal stability of cluster structure between two surveys in 2012 and 2020 in the UK, noting the shift towards the Concerned cluster.…”
Section: Introductionsupporting
confidence: 56%
“…This finding was supported by Liu et al [11], who explored attitudes to climate change risk using the UK Household longitudinal study for 2012 and 2020. Liu et al [11] identified the temporal stability of cluster structure between two surveys in 2012 and 2020 in the UK, noting the shift towards the Concerned cluster. They found that the perception that climate change was a low risk was a barrier to mitigation efforts, emphasising that understanding public attitudes towards climate change was important for policy makers in order to design policy to reduce emissions.…”
Section: Introductionsupporting
confidence: 56%
“…A similar tendency could be observed in the UK: 28% of people in 2011 questioned the ex-istence of climate change. This number declined to a modest size of 6% in 2018 [34]. The same tendency could also be observed in Norway, as climate change doubters dropped from 4.4% in 2018 to 2.4% in 2019 [35].…”
Section: Attitudes and Fossil Resources: Comparing The Danish Case Wi...mentioning
confidence: 57%
“…2_3_4 To date, the study of factors associated with climate risk perceptions has focused primarily on the rich world. 5 For example, research conducted in the United States, 6 -7 -8 Australia, 9 -10 and the United Kingdom 11 - 12 has shown risk perception in a uent democracies to be in uenced by both cognitive 13 and experiential processes. 14 While these ndings enhance our comprehension of climate change risk perceptions, their applicability might be limited to speci c countries and cultures.…”
Section: Introductionmentioning
confidence: 99%